Cantor on Infinitesimals. Historical and Modern Perspective - Błaszczyk, Piotr; Fila, Marlena (Bulletin of the Section of Logic, 2020)
In his 1887's Mitteilungen zur Lehre von Transfi niten, Cantor seeks to prove inconsistency of infi nitesimals. We provide a detailed analysis of his argument from both historical and mathematical perspective. We show that while his historical analysis are questionable, the mathematical part of the argument is false.